Environmental health engineering in the tropics - Cairncross, Sandy; Feachem, Richard G. (Chichester ; New York : J. Wiley, 1993)
This book is about: Health and pollution; Water supply; Environmental modifications and vector-borne diseases; ...
Keywords: Environmental health; Sanitary; Sanitary engineering -- Tropical conditions; Sanitary engineering -- Developing countries